Chronic myeloid leukemia in an adult ghanaian with sporadic neurofibromatosis 1 - Edeghonghon E Olayemi; Amma A Benneh; Michael E Acquah; Paul K Mensah (Wolters Kluwer Medknow Publications, 2011)
Patients with neurofibromatosis type 1 (NF1), a common, progressive, autosomal dominant neurocutaneous disorder, are predisposed to malignancies. Several types of hematologic malignancies have been described in them. However, to date there has been no report to the best of our knowledge of a patient with NF1 developing chronic myeloid leukemia (CML). We present an adult Ghanaian with NF1, who subsequently developed CML. Relevance of the case report is discussed.